A Delphi-based approach for detecting key e-learning trends in postgraduate education: The Spanish case. Issue 6 (10th July 2017) - Lopez-Catalan, Blanca; Bañuls, Victor A.
Abstract : Purpose: The purpose of this paper is to present the results of national level Delphi study carried out in Spain aimed at providing inputs for higher education administrators and decision makers about key e-learning trends for supporting postgraduate courses. Design/methodology/approach: The ranking of the e-learning trends is based on a three-dimensional analysis that combines the cost of implementation, the impact of each trend on learning outcomes and the diffusion forecast among postgraduate courses in the time horizon. The authors use the Delphi method for managing an expert panel. Findings: Mobile learning, gamification, social media and open education are found as some of the key e-learning trends that might have greater educational impacts in postgraduate programs in the next years. These results are expected to help educational institutions to plan future positioning strategies depending on their starting positions, resources and intentions to innovate. Originality/value: Educational managers and planners need to identify priority issues and principal trends in higher education in order to raise their innovative offer and to maintain competitiveness. The results might help them. Moreover the indicator and the methodological approach is a novelty in the field.